Which dominant teaching style are you?: A preliminary study among practitioners at a higher education institution - Zuraina, Ali; Noor Azida, Sahabuddin (JERiS, 2020)
Knowing a practitioner’s teaching style in delivering contents matter to their respective students is vital. Practitioners need to regard that assessing their teaching styles as their personal inventories. Such may assist them in identifying their teaching styles to address their students’ diverse learning styles. The current study reports on practitioners’ styles of teaching in Universiti Malaysia Pahang. Data was collected among five (5) lecturers who are teaching one of the computer science subjects at the university. A questionnaire was employed to gauge the lecturers’ teaching style wherein they were required to identify their teaching styles to be Expert, Formal Authority, Personal Model’, Facilitator, or Delegator. The results of the study revealed that the majority of them demonstrate a single teaching style. Yet, one (1) lecturer employed various teaching styles when delivering content to the students. In other words, overall, these lecturers demonstrate a strong teaching style as an Expert, Facilitator, or different dominant teaching styles. The study implies that assessing the lecturers’ teaching styles is essential as it ensures engagement from students in the learning process of the latter. Equal important is that lecturers need to try employing different styles of teaching to meet the objectives of their lessons.